2011
DOI: 10.2147/ijn.s23392
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of graphene hydrogel via hydrothermal approach as a scaffold for preliminary study of cell growth

Abstract: Background: Three-dimensional assembly of graphene hydrogel is rapidly attracting the interest of researchers because of its wide range of applications in energy storage, electronics, electrochemistry, and waste water treatment. Information on the use of graphene hydrogel for biological purposes is lacking, so we conducted a preliminary study to determine the suitability of graphene hydrogel as a substrate for cell growth, which could potentially be used as building blocks for biomolecules and tissue engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(64 citation statements)
references
References 39 publications
0
64
0
Order By: Relevance
“…Biologists show keen interest in graphene, and various studies have been carried out to investigate its biocompatibility with cells (eg, A549 mammalian cell line on graphene and graphene oxide [GO] paper, NIH-3T3 mouse fibroblast cells on graphene-carbon nanotube, L929 mouse fibroblast cells on graphene-and GO-polyaniline and graphene-reinforced chitosan, ARPE-19 retinal pigment epithelium cells on GO-glucose oxidase, A549 human lung carcinoma epithelial cells on GO, nano-reduced GO functionalized noncovalently by amphiphilic PEGylated polymer chains, and nano-GO covalently PEGylated on U87MG human glioblastoma and MCF-7 human breast cancer cell lines). 1 Our recent work has indicated that graphene, in the form of a three-dimensional structure, may be a promising scaffold for cell growth. 1 In addition to biocompatibility investigations, the use of graphene has been extended to bacterial eradication, including Escherichia coli, Staphylococus aureus, Pseudomonas aeruginosa, and Bacillus cereus.…”
Section: Introductionmentioning
confidence: 99%
“…Biologists show keen interest in graphene, and various studies have been carried out to investigate its biocompatibility with cells (eg, A549 mammalian cell line on graphene and graphene oxide [GO] paper, NIH-3T3 mouse fibroblast cells on graphene-carbon nanotube, L929 mouse fibroblast cells on graphene-and GO-polyaniline and graphene-reinforced chitosan, ARPE-19 retinal pigment epithelium cells on GO-glucose oxidase, A549 human lung carcinoma epithelial cells on GO, nano-reduced GO functionalized noncovalently by amphiphilic PEGylated polymer chains, and nano-GO covalently PEGylated on U87MG human glioblastoma and MCF-7 human breast cancer cell lines). 1 Our recent work has indicated that graphene, in the form of a three-dimensional structure, may be a promising scaffold for cell growth. 1 In addition to biocompatibility investigations, the use of graphene has been extended to bacterial eradication, including Escherichia coli, Staphylococus aureus, Pseudomonas aeruginosa, and Bacillus cereus.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the processed graphene composites showed acceptable biocompatibility [18]. (ii) Graphene hydrogels [28]. TWEEN: polyoxyethylene sorbitan laurate.…”
Section: Utilization Of the Complex Physical Properties Of Graphenementioning
confidence: 99%
“…Thus, graphene hydrogels are frequently used as tissue scaffolding materials. Lim et al [28] made a three dimensional graphene hydrogel using a hydrothermal method. As expected, the porous structure of the hydrogels could be shaped by the stiffness of hydrogel materials.…”
Section: Utilization Of the High Electrical Conductivity Of Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…13 GO contains a large amount of hydrophilic groups on its edge or basal planes; thus, sheets of small size and lower concentrations should be much more biocompatible. These properties make GO extremely attractive to a large swath of scientists with new applications in the fields of drug delivery, [14][15][16][17][18][19][20][21][22][23][24][25] parasitology, 26,27 tissue engineering (TE), [28][29][30][31][32][33][34][35] antibacterials, [36][37][38][39][40][41][42][43][44] cancer therapy, [45][46][47][48][49] sensors [50][51][52][53][54][55][56][57][58][59][60][6...…”
Section: Introductionmentioning
confidence: 99%